The Influence of E-Commerce, Product Innovation, & Business Networks on Increasing the Profits of Clothing MSMEs in Bojonegoro Regency (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This study aims to determine the role of e-commerce, Product Innovation, & Business Networks on the ability of MSMEs to increase business profits.This study also aims to determine the extent to which the implementation of e-commerce can expand the market, increase sales, and contribute to increasing profits for clothing MSMEs in Bojonegoro Regency..This study uses a quantitative approach with descriptive and analytical research types. Data were collected through questionnaires distributed to owners and actors of clothing MSMEs in Bojonegoro Regency. The data analysis technique used is multiple linear regression analysis to see the relationship between existing variables (e-commerce, product innovation, business networks) with increasing MSMEs profits with long-term projections. Based on the discussion and analysis of the influence of e-commerce, product innovation, and business networks on increasing the profits of clothing MSMEs in Bojonegoro Regency, it can be concluded that the e-commerce variable does not have a significant effect on the income variable of clothing MSMEs in Bojonegoro Regency. Then product innovation has a significant effect on increasing MSME profits. Furthermore, business networks also have a significant effect on increasing MSME profits.